Relation-Theoretic Contractions Employing a New Pair of Shifting Distance Functions with Applications to Second-Order Ordinary Differential Equations - Faizan Ahmad Khan; Fahad M. Alamrani; Esmail Alshaban; Ebrahem A. Algehyne; Musaad S. Aldhabani (Journal of Mathematics)
The objective of the paper is to present some fixed point results verifying a relational contraction utilizing certain shifting distance functions and via a generalized class of transitive relations. Our outcomes sharpen, extend, modify, and enrich many well-known results. To demonstrate the utility of our results, several examples are provided. We employed our results finding out a unique solution of second-order ordinary differential equations prescribed with specific boundary conditions.